The Role of Islamic Faith-Based Organization in Building Solidarity and Resilience among People of Different Faiths in Northeast Thailand: A Case Study of Foundation for Education and Development of Muslims in Northeast Thailand-FEDMIN - IMRON SOHSAN (Jurnal Studi Pemerintahan, 2014)
The purposes of this paper are to examine therole of FEDMIN in building solidarity andresilience between Muslims and Buddhists andto find a model of peaceful coexistence amongpeople of different faiths in northeast Thailandcalled “Isan region”. The research area wasfocused on the peaceful coexistence betweenMuslims and Buddhist in particular in Ban NongMuen Tao village, Mueang, Udon Thaniprovince. The study found that there were fourimportant roles of FEDMIN in building solidarityand resilience among people of different faiths.Firstly, demonstrating the real image of Islamand Muslims to the other people of differentfaiths through the FEDMIN leaders’ role andpersonality in practicing peaceful coexistence,FEDMIN’s Santhitham Wittaya School, Muslimvillage model, which were described as “anintellectual contribution of Muslim communityfor the public”, FEDMIN Muslim area as a fieldtrip attraction to the Authorities. Secondly,encouraging Muslims and Buddhists to set up asuitable atmosphere of dialogue of action basedon socially engaged Islam and Buddhismconcept which was demonstrated by the faithbasedcommunity forum as “comfort space” inwhich a suitable atmosphere of dialogue ofaction can exist. Third, empowering religiousinstitution to play a vital role in preaching theprinciples of peaceful coexistence to believersbecoming citizen of the society through Islamicsermon- Khutbah, Islamic class, establishingSanthitham Wittaya school as a substantivecontribution from Muslim community to thepublic, and Community Radio Station project asa positive media which supported to create anatmosphere of citizenship among people ofdifferent faiths in the village.